Faith and fatherland: parish politics in Hitler's Germany - Jantzen, Kyle (Religion and politics in the Third Reich, 2008)
Introduction -- Faith and fatherland through the eyes of clergy -- National socialism as a catalyst for German Protestant renewal? -- Pastoral appointments and the local church struggle -- Clerical responses to euthanasia and anti-semitism -- The church struggle in Nauen, Brandenburg -- The church struggle in Pirna, Saxony -- The church struggle in Ravensburg, Württemberg